Leading for mindfulness. (February 2023) - Schussler, Deborah L.; Krisch, Karen; Mahfouz, Julia; Baelen, Rebecca N.; Gould, Laura Feagans
In the last 15 years, mindfulness programs have become more popular in schools. However, bringing mindfulness into schools involves more than selecting a curriculum. It entails creating the conditions for mindfulness that requires a particular kind of leadership: the capacity to lead for and with mindfulness. Authors Deborah L. Schussler, Karen Krisch, Julia Mahfouz, Rebecca N. Baelen, and Laura Feagans Gould highlight common principles and practical examples from educational leaders engaging in this work and share some of the emerging research into mindfulness in education .